Controversial Issues in Health Care Policy. - Kronenfeld, Jennie J. (Controversial issues in public policy., 1992)
In the last 35 years, health care in the US has grown into a multi-billion dollar industry. Americans view access to health care as important and take pride in their excellent medical care technology. However, there is growing consensus that the US health care system is in crisis - but there is far less agreement on what to do about it. This book examines the major controversies confronting American society, health care professionals and policy makers: access to health care, costs and financing health care and the quality of health care. Kronenfeld discusses whether the system can solve these.